|x+1| - |x| + 3|x-1| - 2|x-2| = |x+2|
1) x < -2
(-x-1) - (-x) + 3(1-x) - 2(2-x) = -x-2
-x-1+x+3-3x-4+2x = -x-2
-x-2 = -x-2 - это верно для всех x < -2
2) x € [-2; -1)
(-x-1) - (-x) + 3(1-x) - 2(2-x) = x+2
-x-1+x+3-3x-4+2x = x+2
-x-2 = x+2; x = -2 - подходит.
3) x € [-1; 0)
(x+1) - (-x) + 3(1-x) - 2(2-x) = x+2
x+1+x+3-3x-4+2x = x+2
x = x+2 - решений нет
4) x € [0; 1)
(x+1) - x + 3(1-x) - 2(2-x) = x+2
1+3-3x-4+2x = x+2
-x = x+2; x = -1 - не подходит
5) x € [1; 2)
(x+1) - x + 3(x-1) - 2(2-x) = x+2
1+3x-3-4+2x = x+2
5x-6 = x+2; x = 2 - не подходит.
6) x >= 2
(x+1) - x + 3(x-1) - 2(x-2) = x+2
1+3x-3-2x+4 = x+2
x+2 = x+2 - это верно для всех x >= 2
ответ: (-oo; -2] U [2; +oo)
18√7 - 9√28 = 18√7 - 9√(4*7) = 18√7 - 18√7 = 0
5 - √34 = √25 - √34 < 0
2√5 = √4*5 = √20
3√2 = √8*2 = √18
сравним √7 + √11 и √20 так как оба положительны то возведем в квадрат
(√7 + √11)² ∨ √20 ²
7 + 2√77 + 11 ∨ 20
2√77 ∨ 2 видно что 2√77 > 2
5-√34, 18√7 - 9√28, 3√2, 2√5, √7 + √11